The convergence of contemporary Indonesian political parties - Fitriyah, Fitriyah; Sweinstani, Mouliza K. D.; Noor, Firman; Romli, Lili; Hanafi, Ridho Imawan; Siregar, Sarah Nuraini (Frontiers in Political Science, 2025)
In terms of ideology, contemporary political parties in Indonesia can no longer be easily categorized as either Islamic or secular nationalist parties. Political parties are currently aligned with the Pancasila ideology. Using a qualitative approach that includes interviews with party elites at both the central and provincial levels— and applying variables that differ from those used in traditional dichotomous classifications of political party ideologies—this study demonstrates that there has been a convergence of Islamic and national values within political parties in Indonesia. This convergence is evident in two aspects: value infusion, reflected in the content of cadre training materials, and political behavior, which can be seen from implementation or articulation of an ideology, including those related to the party’s vision or mission. Therefore, it can be concluded that, at present, no political party exclusively prioritizes either the national or the religious dimension. However, this does not mean that all political parties occupy the same ideological position. Gradations among them can still be observed, although not in a dichotomous manner, with parties distributed along a continuum from the extreme left to the extreme right.